PENGARUH PEMBERIAN KOMPENSASI, FASILITAS KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA UD. AL MUBAROKAH PARE - Rasitania, Tika; Septa Wihara, Dhiyan; Kurniawan, Rony (Universitas Nusantara PGRI Kediri, 2023)
The continuous development of the era and the increasingly real competition of corporate organizations seem to be a challenge for companies that already exist or are just starting out. Indonesia is one of the countries that is included in the competition for the Asean Economic Community (AEC) and that means whether Indonesia wants it or not, it must remain ready for this situation by continuing to develop the potential of existing human resources and continue to prepare for the potential of human resources that do not yet exist. The purpose of this study was to determine and analyze the effect of compensation, work facilities and work environment on employee performance at UD. AL Mubarokah Pare simultaneously or partially. This study uses an associative or causality quantitative approach using research methods using multiple linear regression analysis. The population in this study were all UD employees. AL Mubarokah Pare as many as 30 employees. The sample in this study were 30 employees. The sampling technique used was saturated sampling. The results of this study show that partially the work compensation variable has a significant effect on employee performance, the facility variable has a significant effect on employee performance, and the work environment variable has a significant effect on employee performance. Simultaneously the variables of compensation, work facilities and work environment have a significant effect on employee performance at UD AL Mubarokah Pare.